Da li shi nü hai - Chiang, I-Tsun,Maoyu (Ba ba wen hua, 2021)
Hercules thought he lost his entire family after completing The Twelve Labours. Fortunately, his sister Athena foresaw it and hid his daughter Grapho in the world for him. Although Grapho cannot walk, she has other strengths. What will Grapho use her special ability to create her new life for?
In chinesischer Schrift mit Umschrift in Fu yin zhu hao/ Guo yu zhu yin
Keywords: Bilderbuch; Adaption; Mythologie